Biofloc technology on the intensive aquaculture of bronze corydoras ornamental fish Corydoras aeneus with different stocking densities - Iis Diatin; Muhammad Agus Suprayudi; Tatag Budiardi; Enang Harris; Widanarni Widanarni (Jurnal Akuakultur Indonesia)
ABSTRACT